2010
DOI: 10.1590/s0034-737x2010000600002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de absorvedor de etileno na conservação de mamão "Golden", armazenado à temperatura ambiente

Abstract: Ethylene absorber in conservation of 'Golden' papaya stored at room temperatureThe objective of this work was to determine the most efficient potassium permanganate (KMnO 4 ) dose associated with plastic packaging in delaying processes related to ripening of 'Golden' papaya stored under room temperature. Groups of three fruits with unitary average weight of 278,8±18,9 g were wrapped in low-density polyethylene bags with KMnO 4 sachets, in the doses of 0.0, 1.0, 2.0, 3.0 and 4.0 g/bag. The wrapped fruits were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
0
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
2
0
0
2
Order By: Relevance
“…1A). This lower loss in the treated fruits is possibly related to the decrease of the respiratory activity, due to the lower accumulation of ethylene inside the packages, agreeing with Silva et al (2010) that in work with 'Golden' papaya observed loss of mass for the upper control treatment (5.5%) to treatments with KMnO 4 (3.7%) after 15 days of storage at 25° C.…”
Section: Resultssupporting
confidence: 89%
“…1A). This lower loss in the treated fruits is possibly related to the decrease of the respiratory activity, due to the lower accumulation of ethylene inside the packages, agreeing with Silva et al (2010) that in work with 'Golden' papaya observed loss of mass for the upper control treatment (5.5%) to treatments with KMnO 4 (3.7%) after 15 days of storage at 25° C.…”
Section: Resultssupporting
confidence: 89%
“…This fact may be due to the reduction of the O 2 level inside the container promoted by the sachet, leading to an anaerobic condition, causing darkening in the MP-sprout. This color change was also observed by Silva et al (2003) when using O 2 -absorbing sachets to preserve minimally processed cabbage leaves.…”
Section: Resultssupporting
confidence: 52%
“…O mesmo ocorreu em temperatura ambiente, sendo que o efeito foi observado em frutos colhidos em estádios menos avançados de maturação. Silva et al (2010) concluem que o permanganato de potássio foi eficiente como absorvedor de etileno e manteve os mamões 'Golden' verdes durante 15 dias de armazenamento a 20 °C, apresentando melhor aspecto externo em relação aos frutos não tratados com o absorvedor de etileno.…”
Section: Resultsunclassified